Nitrogen use in double cropping soybean with non-fertilized winter oilseed crops - Liu, Ronghao; Gregg, Stephen; Garcia y Garcia, Axel (International Journal of Agricultural and Biological Engineering, 2023)
Sustainable intensification of cropping systems is a strategy to increase productivity and reduce disservices of conventional agroecosystems. Camelina [Camelina sativa (L.) Crantz] and field pennycress (Thlaspi arvense L.) are winter annual oilseed crops well suited to fill the fallow period between corn (Zea mays L.) and soybean [Glycine max (L.) Merr.] in the U.S. northern Corn Belt, but resources use could limit their addition. A 2-year study was conducted from 2015 to 2017 in the U.S. upper Midwest to evaluate the effect of double cropping on winter oilseed crops and soybean productivity and economic performance. Treatments included relay- and sequential-cropped soybean with winter camelina and field pennycress, and monocrop soybean as control. Biomass and grain yield of winter oilseed crops were not affected by cropping system. Averaged over years and cropping systems, winter camelina resulted in more biomass, nitrogen (N) uptake and grain yield by 240, 186 and 139% respectively, compared to field pennycress. Soybean biomass, N uptake and yield were higher in relay relative to sequential cropping. Relay soybean resulted in similar total grain yield (soybean + winter oilseed crop) compared to monocropped soybean. Double cropping soybean could maintain net return compared to monocropped soybean. Results indicate that double cropping winter oilseed crops with soybean can be economically viable in the U.S. upper Midwest. Yet, research aimed at optimizing yield through N and water use while improving ecosystem services is needed.Key words: camelina, pennycress, relay cropping, multiple cropping, winter oilseedDOI: 10.25165/j.ijabe.20231602.7547Citation: Liu R H, Gregg S, Garcia y Garcia A. Nitrogen use in double cropping soybean with non-fertilized winter oilseed crops. Int J Agric & Biol Eng, 2023; 16(2): 159–164.